PARTICIPANTS ON THE MARGINS: EXAMINING THE USE OF SNAPCHAT, FACEBOOK, AND TWITTER AMONG POLITICAL NEWCOMERS DURING THE STUDENT FERGUSON PROTESTS - Schofield Clark, Lynn (AoIR Selected Papers of Internet Research, 2015)
This article presents a case study of a group of high school aged students of color as they considered participating in a walkout, as they observed others in their peer networks who were making similar decisions about participating, and as they then interpreted that participation after the fact. It explores the role that the social media platforms Snapchat, Facebook, and Twitter played in this decision-making and in reflections about their own participation. It therefore aims to contribute to understandings of how social movements develop, following Palczewski (2011), who argued that scholars need to pay attention to both state-focused political activism as well as culturally driven discursive politics.